2008
DOI: 10.1055/s-2008-1027157
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Aetiology and Associated Co-Morbidities of Elevated Aminotransferases in a German Cohort of Orthopaedic Surgery Patients

Abstract: Our study proved a high prevalence of elevated aminotransferases in orthopaedic surgery patients, most frequently caused by NAFLD, and its association with a high rate of concomitant diseases. Thus, abnormal liver enzymes should lead to a focused screening for concomitant diseases such as diabetes, hypertension and coronary atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
0
11
0
4
Order By: Relevance
“…Through a detailed review of published literature and the analysis of subpopulations, an anti‐HCV prevalence estimate of 0.5% (0.3–0.9%), corresponding to 410 000 (246 000–738 000) anti‐HCV infections, was estimated for 2012 (Table ) . A national study conducted in 2011, the German Health Interview and Examination Survey for Adults (DEGS1), estimated the anti‐HCV prevalence to be 0.3% (0.1–0.5%) .…”
Section: Resultsmentioning
confidence: 99%
“…Through a detailed review of published literature and the analysis of subpopulations, an anti‐HCV prevalence estimate of 0.5% (0.3–0.9%), corresponding to 410 000 (246 000–738 000) anti‐HCV infections, was estimated for 2012 (Table ) . A national study conducted in 2011, the German Health Interview and Examination Survey for Adults (DEGS1), estimated the anti‐HCV prevalence to be 0.3% (0.1–0.5%) .…”
Section: Resultsmentioning
confidence: 99%
“…Both studies found elevated prevalence in females, although the variance between genders was not statistically significant. A study of 1064 orthopaedic surgery patients in east Germany identified no cases of HCV, indicating the potential of different prevalence rates in West Germany and East Germany (106).…”
Section: Resultsmentioning
confidence: 99%
“…The large National Health and Nutrition Examination Survey (NHANES) III study, representing a civilian noninstitutionalized population in the United States, found a prevalence of 13.5% in HCV-and HBV-negative individuals [19]. A German cohort study of orthopedic surgery patients without chronic viral hepatitis noted a prevalence of 11.3% [20] and in HIV-infected persons without viral hepatitis the prevalence was in the same range with 15% [11]. These figures are in accordance with our study with a prevalence of 13.2% in a single ALT measurement at baseline (data not shown).…”
Section: Discussionmentioning
confidence: 99%